2015
DOI: 10.1016/j.beproc.2014.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Why do adult dogs ‘play’?

Abstract: Among the Carnivora, play behaviour is usually made up of motor patterns characteristic of predatory, agonistic and courtship behaviour. Domestic dogs are unusual in that play is routinely performed by adults, both socially, with conspecifics and with humans, and also asocially, with objects. This enhanced playfulness is commonly thought to be a side effect of paedomorphosis, the perpetuation of juvenile traits into adulthood, but here we suggest that the functions of the different types of play are sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 60 publications
(75 reference statements)
2
40
0
1
Order By: Relevance
“…Both HDPI and TRAIN have likely been important selection criterion for the working breeds. The adult dog's play with its handler is important for both the social interaction and as a reward during training sessions (Bradshaw et al, 2015), and thus an important factor for success in the working dog. Svartberg (2006) also found that more working merits were associated with higher scores for playfulness and trainability.…”
Section: Sociability Playfulness and Trainabilitymentioning
confidence: 99%
“…Both HDPI and TRAIN have likely been important selection criterion for the working breeds. The adult dog's play with its handler is important for both the social interaction and as a reward during training sessions (Bradshaw et al, 2015), and thus an important factor for success in the working dog. Svartberg (2006) also found that more working merits were associated with higher scores for playfulness and trainability.…”
Section: Sociability Playfulness and Trainabilitymentioning
confidence: 99%
“…Canids, such as dogs and wolves, are unusual in that they exhibit high frequencies of play behaviors even as adults (for a review of dog play see [19,20]). Furthermore, they exhibit one of the most stereotyped and easily recognizable carnivore play signals, the play bow [21].…”
Section: Introductionmentioning
confidence: 99%
“…As Bradshaw et al. [71] review, play in dogs correlates with a number of variables indicating positive well-being, including obedience indicative of close social bonds with owners. Therefore, the centrality of the ‘Playful’ descriptor in our network analyses holds an interesting organizational position in the behavioural phenotype of police dogs.…”
Section: Discussionmentioning
confidence: 99%